The Hereditary Hyperferritinemia-Cataract Syndrome in 2 Italian Families - Katia Perruccio; Francesco Arcioni; Carla Cerri; Roberta La Starza; Donatella Romanelli; Ilaria Capolsini; Maurizio Caniglia (Case Reports in Pediatrics)
Two 8- and 9-year-old brothers were referred to the Pediatric Oncology Unit, Perugia General Hospital, because of hyperferritinemia. Both had a history of bilateral cataract and epilepsy. Genetic investigation revealed two distinct mutations in iron haemostasis genes; homozygosity for the HFE gene H63D mutation in the younger and heterozygosity in the elder. Both displayed heterozygosity for C33T mutation in the ferritin light chain iron response element. A 7-year-old boy from another family was referred to our unit because of hyperferritinemia. Genetic analyses did not reveal HFE gene mutations. Family history showed that his mother was also affected by hyperferritinemia without HFE gene mutations. Magnetic resonance imaging in the mother was positive for iron overload in the spleen. Cataract was diagnosed in mother and child. Further genetic investigation revealed the C29G mutation of the ferritin light chain iron response element. C33T and C29G mutations in the ferritin light chain iron response element underlie the Hereditary Hyperferritinemia-Cataract Syndrome (HHCS). The HFE gene H63D mutation underlies Hereditary Haemochromatosis (HH), which needs treatment to prevent organ damages by iron overload. HHCS was definitively diagnosed in all three children. HHCS is an autosomal dominant disease characterized by increased L-ferritin production. L-Ferritin aggregates accumulate preferentially in the lens, provoking bilateral cataract since childhood, as unique known organ damage. Epilepsy in one case and the spleen iron overload in another could suggest the misleading diagnosis of HH. Consequently, the differential diagnosis between alterations of iron storage system was essential, particularly in children, and required further genetic investigation.